PENGEMBANGAN BUKU SAKU MANAJEMEN WAKTU SEBAGAI MEDIA PEMBELAJARAN BIMBINGAN DAN KONSELING DI SMA ADHYAKSA 1 KOTA JAMBI - Sari, Kurnia Dian (Program Studi Bimbingan dan Konseling FKIP UNJA, 2022)
This study aims to: develop learning media in the form of Guidance and Counseling Pocket Books for high school students of class XI with Time Management material, find out the feasibility of Pocket Books as learning media based on the assessment of material experts, media experts, and students from the aspects of content, language, presentation, and graphics. This research is a development research or Research and Development (R&D) adapted from the ADDIE development model. The data collection technique in this development research is through observation, interviews, and questionnaires. The data obtained from the questionnaires were analyzed descriptively qualitatively and quantitatively. The results of the study show that there are five stages of making a Pocket Book, namely: 1) Analysis, in this stage it contains an analysis of needs, objectives and materials, 2) Design, this stage includes media specifications, material structure, and layout and book design. pocket, 3) Development, this stage includes making a product which is then validated by a team of experts with the results of the quality of the book being said to be good, 4) Implementation, and 5) Evaluation. Thus the product is declared feasible, in terms of the design of the media and material for the pocket book that was developed and is worthy of being tested. From the results of the student response questionnaire, the percentage score of 77.87% (Good), from the results of the data students gave a very good response to the product developed. This electronic module that has been developed is suitable for use in learning activities other than being used as a medium for independent learning both in the classroom and outside the classroom.